The Effect of Promotion Mix Costs on Room Occupancy Rates in Hotels in Jakarta - Cantika, Ni Putu Ayu Chandra; Kalpikawati, Ida Ayu; Jata, I Wayan (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This study was conducted in one of the hotels in Jakarta, aiming to examine the inefficiency of promotional mix costs on room occupancy rates. This quantitative study with secondary time series data uses statistical tests including t-test, F-test, and coefficient of determination. The results show that promotional costs have a significant positive effect on room occupancy rates of 58%. Promotion components such as sales promotion, personal selling, advertising, and public relations all have a significant effect. Other factors not studied affect 42% of the variation in occupancy rates.